G292(P) Surveillance of sleep disordered breathing for young children with down syndrome within a geographically-defined area. (25th October 2020) - Bryson, L; Sanner, J; Barclay, M; Nisbett, C; Robertson, C; Bhatt, J; Marder, E; Thomas, D; Hurley, M
Abstract : Aims: Our Children's Hospital Down syndrome service cares for all young children with Down syndrome within the County boundary. Children with Down syndrome are at risk of sleep disordered breathing. Guidelines recommend overnight oximetry in infancy and annually until the ages 3–5 years. To audit adherence to guidelines regarding surveillance of sleep disordered breathing. To estimate the prevalence of sleep disordered breathing, severity and requirement of intervention within our population. Methods: We undertook a retrospective case note audit of children cared for within the Down syndrome service 2010–2019. Studies undertaken outside of the surveillance period (older than 5 years) were not included. Results: 102 children, aged between 27 days and 5.8 years, underwent 343 overnight oximetry studies (range 1–11 studies per child). Comorbidities included congenital heart disease (62); pulmonary hypertension (12); prematurity (8); airway abnormality not including adenotonsillar hypertrophy (10). Only two children did not have a significant comorbidity. 41 children had a study suggestive of sleep disordered breathing. 18 children underwent adenotonsillectomy. Three children required tracheostomy and invasive ventilation. 4 received non-invasive ventilation. 16 children did not have a study (of whom 9 moved out of area). Conclusion: The guidelines were followed in 93% of cases. The proportion of children with significant comorbidities was high. One third of children in this group had sleep disordered breathing of whom over half required significant intervention.